2018
DOI: 10.1055/s-0038-1655751
|View full text |Cite
|
Sign up to set email alerts
|

Hemifacial Trigeminal Pain Referred from Occipital Neuralgia Due to Compression of the Greater Occipital Nerve by the Occipital Artery

Abstract: Although pathologic vascular contact between the occipital artery and the greater occipital nerve (GON) at the crossing point in the nuchal subcutaneous layer can cause occipital neuralgia, referred hemifacial trigeminal pain from chronic occipital neuralgia owing to this cause is extremely rare.A 61-year-old female patient with left-sided occipital neuralgia for 4 years presented with a new onset of left-sided hemifacial pain. Decompression of the left GON from pathologic contacts with the occipital artery re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 15 publications
1
36
1
Order By: Relevance
“…In 2017, Ko et al reported a case of hemifacial trigeminal pain referred from ON due to compression of the greater occipital nerve by the occipital artery [13]. The occipital artery was superficial to the greater occipital nerve, creating a crossing point and a constricting vascular loop.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Ko et al reported a case of hemifacial trigeminal pain referred from ON due to compression of the greater occipital nerve by the occipital artery [13]. The occipital artery was superficial to the greater occipital nerve, creating a crossing point and a constricting vascular loop.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical significance of the GON entrapment at and around the trapezial canal has been stressed repetitively during the last two decades. It is a well known etiology of occipital neuralgia 8,11,14,17,18) . In addition, entrapment of the GON was reported to be associated with cervicogenic headache, migraine headache 12) , chronic headache 6) , and referred trigeminal pain from occipital neuralgia 8,11,14) .…”
Section: Greater Occipital Nerve and Its Entrapmentmentioning
confidence: 99%
“…This prediction can be judged to be credible as the patient's symptoms have improved through decompression of the GON. We have experienced several cases that hemifacial pain, in addition to the occipital neuralgia, is improved by decompression of the GON 8,9,11,14,15) . Although it has already been mentioned that the pain of occipital neuralgia may be referred to the fronto-orbital area through trigeminocervical interneuronal connections in the trigeminal spinal nuclei 1) , referred facial pain in addition to occipital neuralgia has not been accurately reported 8,9,11,14,15) .…”
Section: Differential Diagnosis Of Chronic Gon Entrapmentmentioning
confidence: 99%
See 2 more Smart Citations